Investor horizons, long-term blockholders, and corporate social responsibility - Gloßner, Simon (Journal of Banking & Finance, 2019)
This paper investigates whether or not shareholders benefit from corporate social responsibility (CSR) by studying the effect of institutional investors on CSR. After all, arguing against CSR is hard when investors push for it. I find that longer investor horizons lead to significantly more CSR. This positive effect, however, is moderated by long-term investors who hold large ownership blocks. Long-term blockholders ensure, through monitoring, that managers do not blindly increase CSR, but rather that managers pursue a CSR strategy that reduces the risk of costly incidents. A battery of robustness tests indicates causality. Overall, these findings indicate that CSR is in the interests of long-term investors if CSR prevents incidents.